2013
DOI: 10.1007/s00464-013-2794-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of epidural analgesia on bowel function in laparoscopic colorectal surgery: a systematic review and meta-analysis

Abstract: Despite of some beneficial effect of epidural analgesia on return of bowel function and pain in laparoscopic surgery, it does not affect LOS, which is multifactorial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 55 publications
1
40
1
2
Order By: Relevance
“…On one hand, six studies used epidural analgesia, which showed wide acceptance. The beneficial effect of epidural analgesia in pain control has also been confirmed by many studies [40, 41]. On the other hand, epidural analgesia during laparoscopic surgery is not advocated by some authors.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…On one hand, six studies used epidural analgesia, which showed wide acceptance. The beneficial effect of epidural analgesia in pain control has also been confirmed by many studies [40, 41]. On the other hand, epidural analgesia during laparoscopic surgery is not advocated by some authors.…”
Section: Discussionmentioning
confidence: 89%
“…The meta-analysis conducted by Levy et al [40] suggested that no analgesia protocol showed more overall benefits than did other protocols during laparoscopic surgery. Another meta-analysis showed that epidural analgesia fails to shorten the hospital stay following laparoscopic colorectal surgery [41]. Moreover, even Kehlet [2], who initiated FTS, demonstrated that epidural analgesia might not be necessary in laparoscopic colorectal surgery and can be replaced by non-opioid analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 A multimodal epidural infusion comprising drugs with different pharmacological pathways is more effective than a single-agent infusion. The combination of local anesthetics and adjuvants provides both intraoperative and postoperative analgesia after a wide range of surgeries (e.g., thoracic, abdominal, lower limb).…”
Section: Developmentsmentioning
confidence: 99%
“…lidocaine with epidural bupivacaine in relation to resumption of bowel motility. The authors found no differences with respect to the start of bowel movements and concluded that the favorable effects of this type demonstrated for epidural analgesia [22] can also be achieved with i.v. lidocaine.…”
Section: Effects On Bowel Motility After Visceral Surgerymentioning
confidence: 91%